Mechanisms of Omega-3 Polyunsaturated Fatty Acids in Prostate Cancer Prevention - Gu, Zhennan (Hindawi Publishing Corporation, 2013)
This review focuses on several key areas where progress has been made recently to highlight the role of omega-3 polyunsaturated fatty acid in prostate cancer prevention.